2009
DOI: 10.1097/aud.0b013e3181926524
|View full text |Cite
|
Sign up to set email alerts
|

Receptive Vocabulary Development in Deaf Children with Cochlear Implants: Achievement in an Intensive Auditory-Oral Educational Setting

Abstract: Growth curves indicate that children who are implanted by the age of 2 yr can achieve receptive vocabulary skills within the average range for hearing children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
2
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(133 citation statements)
references
References 20 publications
6
114
2
11
Order By: Relevance
“…That is, a frequent explanation for deaf children's delays in language development, social development, and academic achievement is that their hearing losses prevent their acquiring knowledge relevant to those domains by overhearing the conversations of others as well as communication aimed at them (De Raeve, 2016;Holcomb, 2013;Marschark & Hauser, 2012). Although it is difficult to quantify the effects of overhearing the language of others (or not), findings indicating rapid growth in vocabulary following cochlear implantation among deaf children have suggested that the improved hearing provided by cochlear implants (CIs) might be of significant benefit to incidental learning (Connor, Craig, Raudenbush, Heavner, & Zwolan, 2006;Hayes, Geers, Treiman, & Moog, 2009). Neither CI use nor age of implantation has been found to provide significant long-term benefits to vocabulary or world knowledge (Convertino, Borgna, Marschark, & Durkin, 2014), but the potential for improved hearing and spoken language interactions with diverse others may provide benefits to the development of social maturity.…”
mentioning
confidence: 99%
“…That is, a frequent explanation for deaf children's delays in language development, social development, and academic achievement is that their hearing losses prevent their acquiring knowledge relevant to those domains by overhearing the conversations of others as well as communication aimed at them (De Raeve, 2016;Holcomb, 2013;Marschark & Hauser, 2012). Although it is difficult to quantify the effects of overhearing the language of others (or not), findings indicating rapid growth in vocabulary following cochlear implantation among deaf children have suggested that the improved hearing provided by cochlear implants (CIs) might be of significant benefit to incidental learning (Connor, Craig, Raudenbush, Heavner, & Zwolan, 2006;Hayes, Geers, Treiman, & Moog, 2009). Neither CI use nor age of implantation has been found to provide significant long-term benefits to vocabulary or world knowledge (Convertino, Borgna, Marschark, & Durkin, 2014), but the potential for improved hearing and spoken language interactions with diverse others may provide benefits to the development of social maturity.…”
mentioning
confidence: 99%
“…The results from studies conducted on different-aged hearing-impaired individuals from different areas about how individuals who communicate with the hearing-impaired showed that sign language was of vital importance and came first in the communication preferences of hearing-impaired adults who were deaf from birth and had been educated in a school for the deaf. Auditory verbal education has been used widely in recent years parallel with the increase in early diagnosis and hearing-aid implants (Hayes et al, 2009). However, sign-language was used nearly all the time for the hearing-impaired who couldn't benefit from early intervention audio-verbal education opportunities (Parlak, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of the Turkish Sign Language alphabet and studies regarding its use are among these regulations (Kemaloğlu, 2014a(Kemaloğlu, , 2014b(Kemaloğlu, , 2014c. Auditory verbal education has recently been widely used, parallel with the increase in early diagnosis and hearing-aid usage practices for the hearing impaired (Hayes, Geers, Treiman, & Moog, 2009). However, hearing-impaired individuals can be seen who do not sufficiently benefit from early diagnoses or auditory-verbal education opportunities and have been educated in schools for the deaf where sign language was used in nearly 100% of their communications (Parlak, 2011).…”
Section: Sign Language and Its Usagementioning
confidence: 99%
“…During the first three years of life the development of working memory concurs with the expansion of vocabulary and the building of grammatical skills (Engel de Abreu et al, 2011;Hayes, Geers, Treiman, & Moog, 2009;Nakeva Von Mentzer, 2014). These latter skills, as well as pragmatic language skills, display a developmental burst during the following years until the closing of the first sensitive period (Berk, 2009;Nakeva Von Mentzer, 2014).…”
Section: Theoretical Framework Of the Thesismentioning
confidence: 99%